PENGARUH KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DI SMA NEGERI 1 MANOKWARI - Nurlaela Nurlaela; Natalia Aduari; Dirarini Sudarwadi (Cakrawala Management Business Journal, 2021)
As an educational institution, SMA Negeri 1 requires teachers with good pedagogic and professional competence, so as to achieve the desired quality of performance. The purpose of this study was to determine the effect of pedagogic competence and professional competence on teacher performance at SMA Negeri 1 Manokwari partially and simultaneously. This type of research is quantitative with associative problems. The sample in this study were 50 teachers. The data collection method used is a questionnaire, with a non- probability sampling technique and multiple linear regression data analysis. Page | 1 The results of the partial test show that pedagogic competence and professional competence have an effect on teacher performance. This is indicated by a significant value of 0.000 for pedagogic competence and professional competence of 0.034, both of which the probability values of these competencies are smaller than the error rate of 0.05. And the results of the simultaneous test showed that pedagogic competence and professional competence had an effect on teacher performance, it was indicated by a sig f value of less than 0.05 (0.000 < 0.05). Suggestions for SMA Negeri 1 Manokwari to further improve pedagogic competence by frequently conducting training on the use of computers, LCD projectors and adding focusing equipment. And for professional competence by providing room for actualization for every teacher regardless of employment status. Keywords : Pedagogic Competence, Professional Competence, Teacher Performance.